2016
DOI: 10.1016/j.biortech.2016.07.102
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol production by recycled Scheffersomyces stipitis in sequential batch fermentations with high cell density using xylose and glucose mixture

Abstract: Here, it is shown three-step investigative procedures aiming to improve pentose-rich fermentations performance, involving a simple system for elevated mass production by Scheffersomyces stipitis (I), cellular recycle batch fermentations (CRBFs) at high cell density using two temperature strategies (fixed at 30°C; decreasing from 30 to 26°C) (II), and a short-term adaptation action seeking to acclimatize the microorganism in xylose rich-media (III). Cellular propagation provided 0.52gdrycellweightgRS(-1), resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 34 publications
1
23
1
27
Order By: Relevance
“…However, the temperature decrease along sequential fed batches and the sequential fed batches (recycle), together, promoted high xylose consumption, and all xylose content was consumed in third and fourth fed batches. This observation agrees with Santos et al (), which investigated the consumption of glucose and xylose by S. stipitis in sequential batches with temperature decrease concluding that it improves xylose consumption rate. An explanation for why recycling cells or decreasing temperature process can improve xylose consumption is presented by Slininger et al (, ).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…However, the temperature decrease along sequential fed batches and the sequential fed batches (recycle), together, promoted high xylose consumption, and all xylose content was consumed in third and fourth fed batches. This observation agrees with Santos et al (), which investigated the consumption of glucose and xylose by S. stipitis in sequential batches with temperature decrease concluding that it improves xylose consumption rate. An explanation for why recycling cells or decreasing temperature process can improve xylose consumption is presented by Slininger et al (, ).…”
Section: Resultssupporting
confidence: 93%
“…The present study showed ethanol titer of 18.5 g L −1 , productivity of 0.36 g L −1 h −1 and sugar (glucose and xylose) conversion into ethanol of 0.32 g g −1 . These results are lower than that obtained for Santos et al (), Farias et al (), and Slininger et al (), however, it is important highlight that these works were performed in xylose (Analytical grade) and the present work have used sugarcane bagasse hydrolyzate. When the present work is compared with Dussán et al () results it is possible to observe that ethanol titer (7.34 g L −1 ), productivity (0.1 g L −1 h −1 ), and conversion yield (0.16 g g −1 ) attained by using detoxified sugarcane bagasse hydrolyzate in a batch system carried out in bioreactor were lower than results obtained by the present work (please see Table ).…”
Section: Resultscontrasting
confidence: 75%
See 2 more Smart Citations
“…Glucose, xylose, acetic acid, glycerol, xylitol, furfural, and ethanol were measured during the fermentation according to the analytical measurements described below. Yeast concentrations (g/L) and kinetic parameter calculations (Yp/s: xylose conversion factor in ethanol; Y: percentage of ethanol production) were measured and calculated as described by Santos et al [82]. …”
Section: Methodsmentioning
confidence: 99%